Pengaruh Self Efficacy terhadap Kemampuan Pemecahan Masalah dalam Menyelesaikan Soal Skala - Amalia, Hilda; Sari, Indah Puspita (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2024)
The objective of this research was to ascertain the impact of self efficacy on problem solving ability in solving scale problems in class VIIB students of SMP Negeri 5 Cimahi. The subject of this study is 40 students in grade VIIB with 36 random samples. The type of research used is correlation analysis. The research instrument used is by distributing a self-efficacy questionnaire and a test of mathematical problem-solving ability. The data that has been obtained are then analyzed through classical assumption tests, Pearson correlation tests, and significance tests (t-test). Based on the analysis of questionnaire data and the mathematical problem-solving ability test, a correlation test score was obtained which has a sig value of 0.000 and a correlation amount of 0.775 which means that there is a correlation between Self Efficacy and Problem-Solving Ability, this shows that there is a direct correlation between the two variables. In addition, the Sig value was obtained from the t-test with a magnitude of 0.000 which means that the value does not exceed the significance level of 0.05, this shows that there is a unidirectional relationship and has a considerable influence. So it can be concluded that Problem-Solving Ability in solving scale problems is influenced by Self Efficacy